Antibacterial activity of extracts from Calophyllum canum - Darnis, Deny Susanti; Syed Osman Idid, Syed Zahir Idid; Bakhtiar, M. Taher; HA, Mohamed (2009)
The species of the genus Calophyllum (Guttiferae) are mainly distributed in tropical area. Plants from this genus are known as a rich source of secondary metabolite such as xanthones, coumarins, chromenes, flavonoids and triterpenoids. Some of this compounds exhibit significant biological effects antibacterial, antifungal, anti HIV and immunomodulatory activities. Calophyllum canum or Betangur baatu is a forest tree that found in Penisular of Malaysia. The research is aimed to investigate the bioactivity of C. canum extracts against selected bacteria. The chemical constituent of the plant is also investigated. The extracts are tested for their activity to inhibit the growth of Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus. The anti bacterial testing is carried out by disc diffusion method. It is concluded the C. canum has a greater potency to inhibit the growth of bacteria. The results of antibacterial of the extracts will be discussed in this paper.